Effect of a functional food (vegetable soup) on blood rheology in patients with polycythemia - Hamideh Naghedi Baghdar; Mohsen Nematy; Mohammad-Mahdi Kooshyar; Ali Taghipour; Sayyed Abolghasem Sajadi Tabassi; Sadegh Shokri; Roghayeh Javan; Seyed Mohammad Nazari (Mashhad University of Medical Sciences, 2018)
Objective: Key hemorheological variables are associated with several life-threatening diseases including cardio-cerebro-vascular diseases. A diet can influence the blood rheological variables. To compare the effectiveness of a vegetable soup on blood viscosity (BV), hematocrit (Hct), plasma fibrinogen, lipid profile, fasting blood sugar (FBS), and blood osmolarity in patients with polycythemia in comparison to a control group. Materials and Methods: This randomized controlled trial study was conducted at Isar health clinics in Mashhad, Iran, during a 7-month period. Forty male participants (35 to 60 years old) with polycythemia, but without underlying diseases, were included. They randomly assigned to two groups and either received diet/phlebotomy or phlebotomy alone, for 6 weeks. The data were analyzed by SPSS version 16 using parametric tests. Results: A significant reduction in BV at 30s (p 0.001), BV at 40s (p 0.001), BV at 50s (p 0.001), Hct (p 0.001), plasma fibrinogen (p